Towards design principles for project artistry in exploratory sandpit projects: A design-based research perspective - Makhoalibe, Puleng (Research of GSB, 2018)
Organisations are increasingly finding themselves operating in environments that are characterised by higher levels of ambiguity, uncertainty and complexity, as well as environmental and internal changes that are beyond their control (Reeves, 2015). This context is affecting the way in which projects are executed, as project managers are expected to conceive, manage and successfully implement projects within such an environment. An important question to ask is: Are intrinsically unpredictable environments becoming more dominant leading to increase in the complexity of projects? We are now living in a volatile, uncertain, complex and ambiguous (VUCA) world; project management as a field has to overcome significant barriers to change and develop the capacity for more subjective, interactive, and interpretive innovations that appear to be more effective in these settings. The primary question addressed in this study is how the design of exploration projects may be carried out to bring clarity to project objectives and enablers. Design thinking, which is said to embody practices, mind-sets and processes that empower teams to co-create innovative solutions to wicked problems (Rittel and Webber, 1973) has been adopted in this study. Its design principles together with the creative problem-solving principles are combined to create a framework that facilitates design of exploration projects. This study uses design-based research (DBR) to apply the emerging framework to educational sandpit projects. These projects inherit the characteristics of exploration projects which are highly ambiguous toward more innovative, context-relevant, targeted solutions developed by diverse project teams. The study adopted a qualitative, interpretivist approach in order to enhance the design principles emerging from this study through authentic interventions in educational sandpits using DBR as a methodology. The outcome of the study, namely, a project artistry framework, emerged from the iterative process which was undertaken. The framework's value proposition is that it (the framework) had been proven to enable diverse teams to shift the participants' orientation from significant ambiguity and uncertainty to the ability to plan action by co-creating project visions with clear objectives and goals. The project artistry framework reflects the construction of a house and a more holistic framework, which consists of a roof (design process), the pillars required to hold up the roof (design pillars) and the foundational bricks. The design pillars include reflection, creative language, applied imagination, diverging and converging while the foundational bricks include empathy, empowerment, engagement, emergence, experimentation, environment, exploration and exploitation. In addition, an ambiguity acceptance journey is proposed to encourage a tolerance of ambiguity that leads to questioning and inquiry in projects that cultivates fresh insights and innovation in projects. New approaches to project leadership and design are essential to transform the world we live in. Although no panacea, project artistry provides project leaders with a new dimension to understanding the changing conditions that surround their project and envisioning better, innovative solutions to some of the most troublesome challenges facing our projects. It brings together the power of analysis and intuition to synthesize real solutions that not only work but meet the needs of the people. This fresh approach also brings enlightenment and transformation to those engaged in such projects and cultivates creative confidence and fosters collaboration.